Assessing conservation priorities for seahorses in Brazil reveals gaps in current protected areas - Anna Karolina Martins Borges; Vanessa M. Adams; Rômulo Romeu Nóbrega Alves; Tacyana Pereira Ribeiro Oliveira (Conservation Science and Practice)
Abstract Seahorses are rare and threatened marine species facing increasing risks from habitat degradation and overexploitation. Understanding their distribution is critical for effective conservation planning, yet comprehensive studies are limited, including in Brazil. This study aimed to conduct a gap analysis and identify priority areas for seahorse conservation by using species distribution models (SDMs) to map their distribution and guide conservation efforts. Occurrence data and environmental variables were processed to develop SDMs. Conservation gaps were identified by comparing SDM predictions with the existing protected area (PA) network, and priority areas were determined using Marxan software. SDMs revealed species‐specific habitat associations: Hippocampus reidi was found in shallow coastal habitats, such as mangroves, seagrass beds, and rocky shores, across Brazil, particularly in the northeast and southeast; Hippocampus patagonicus occurred in deeper coastal areas, from Rio de Janeiro to Rio Grande do Sul; and Hippocampus aff. erectus was limited to the northeast, primarily inhabiting mangrove and seagrass areas. Conservation gaps were significant, with only 9%, 11%, and 20% of suitable habitats for H. reidi, H. patagonicus, and H. aff. erectus overlapping PAs, even less in strictly protected zones. Priority areas suggest a 17% expansion of the protected area system to meet conservation targets. This study emphasizes the urgent need for targeted strategies to safeguard seahorses and their habitats in Brazil, highlighting the importance of addressing taxonomic uncertainties, filling knowledge gaps, exploring their potential as flagship species, and strengthening protections to mitigate biodiversity loss. These findings provide decision‐makers and stakeholders with actionable insights to ensure the long‐term preservation of these vulnerable species and their habitats.